The Accountant: accountant stereotypes and the effects on students' and accounting professionals' self-image - Tonin, Joyce Menezes da Fonseca (2020)
This research aims to analyze the competencies required by the American Institute of Certified Public Accountants (AICPA) and build collective discourses on these competencies and the stereotypes of the accounting professionals represented in the film The Accountant, 2016. The data collection was done through a questionnaire prepared in Google Docs and made available on Facebook in groups aimed at students and accounting professionals. We obtained 98 valid answers and used the Discourse of the Collective Subject analysis to identify the similarities and divergences between the discourse of students and accounting professionals who watched the film. The findings suggest that both groups point to intelligence, proactivity, and ethical behavior as characteristics positively associated to the professional's profile. These characteristics are linked to the stereotype of the contemporary accountant and indicate a change in the social representation of the professional compatible with the characteristics of the character Christian Wolff, played by Ben Affleck, in the film. Among the negative characteristics is anxiety, which is recurrent in both groups. The findings put into discussion the effects of the cinematographic representation of the accountant on the self-image of students and accounting professionals, highlighting the alteration in this social representation by converging to the characteristics associated to the stereotype of the contemporary accountant.